THE EFFECT OF FINANCIAL STABILITY, NATURE OF INDUSTRY AND TOTAL ACCRUAL ON FRAUDULENT FINANCIAL STATEMENTS - Aprian, Farhan Habib; Fauzi, Achmad; Mardi (Transpublika Publisher, 2023)
This study aimed to investigate the impact of Financial Stability (ACHANGE), Nature of Industry (REC), and Total Accruals (TATA) on fraudulent financial statements, using the Modified Jones model as a proxy. The study used the documentation method to collect data from 55 industry companies listed on the Indonesia Stock Exchange in 2020. Annual financial reports were obtained from the IDX website, and a sample of 34 companies was selected using purposive sampling. Multiple linear regression analysis, prerequisite analysis tests, classical assumption tests, and hypothesis testing were used to analyze the data. The multiple linear regression analysis was used to examine the relationship between variables, while the prerequisite test checked the normal distribution of data, the classic assumption test checked for data acceptability, and the hypothesis test determined the acceptance or rejection of hypotheses. The results revealed that Financial Stability (ACHANGE) and Nature of Industry (REC) had a significant impact on fraudulent financial statements, while Total Accruals (TATA) did not have a significant effect.